2018
DOI: 10.1016/j.fertnstert.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience in a randomized trial of a weekly progesterone vaginal ring versus a daily progesterone gel for luteal support after in vitro fertilization

Abstract: Objective: To assess patient experience and convenience of using progesterone vaginal ring (VR) versus vaginal gel for women requiring luteal phase support during in vitro fertilization (IVF). Design: Post hoc analysis of a prospective, randomized, single-blind, multicenter, phase 3 clinical trial. Setting: Twenty-two U.S. IVF centers. Patient(s): Women undergoing IVF (N ¼ 1,297). Intervention(s): Randomization to weekly VR or daily gel the day after egg retrieval for up to 10 weeks, with fresh embryo transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Aside from the differences in efficacy between oral dydrogesterone and MVP identified in this study, the administration route of oral dydrogesterone may be advantageous as patients usually prefer to use oral preparations compared to vaginal ones [26,57,58]. This may be due to the overall inconvenience [59], administration-related side effects [14,15], and cultural barriers associated with using MVP [9]. Although MVP may be the most prescribed route of luteal phase support administration [7], it may not be the most preferred route of administration since women often find vaginal preparations less appealing than oral administration, particularly due to comfort issues [60].…”
Section: Plos Onementioning
confidence: 93%
“…Aside from the differences in efficacy between oral dydrogesterone and MVP identified in this study, the administration route of oral dydrogesterone may be advantageous as patients usually prefer to use oral preparations compared to vaginal ones [26,57,58]. This may be due to the overall inconvenience [59], administration-related side effects [14,15], and cultural barriers associated with using MVP [9]. Although MVP may be the most prescribed route of luteal phase support administration [7], it may not be the most preferred route of administration since women often find vaginal preparations less appealing than oral administration, particularly due to comfort issues [60].…”
Section: Plos Onementioning
confidence: 93%
“…Even though the study by Ginsburg et al (5) was conducted in 2008-2009, the weekly vaginal ring used in this study is still not clinically available, nor is there any evidence online to indicate that the product ever will be available. The study by Ginsburg et al (5) has clearly demonstrated that the patients found using weekly vaginal rings was more convenient, interfering less with their daily, social, and sexual activities. If the vaginal ring were to become clinically available, the…”
mentioning
confidence: 88%
“…However, a threefold higher rate of vaginal discharge was reported in the vaginal ring group (26). Ginsburg et al explained that women preferred weekly vaginal rings to vaginal gel because they were more convenient with no interference with daily and sexual activities, even though the gel was less difficult and stressful to apply (27). The most common complaints about vaginal progesterone are increased vaginal International Journal of Reproductive BioMedicine Dashti et al…”
Section: Vaginal Progesteronementioning
confidence: 99%